The Ontology of Food and Nutrition System for Pre-School - Lertkrai, Puriwat; Kaewboonma, Nattapong; Lertkrai, Jutaporn (International Journal of Engineering and Technology, 2018)
Nutrition is very important for pre-school children age 1-5 years. At this age, they grow too fast both with body and brain. Structural damages in the body and brain may result if children are underweight or obese. In this research, we propose an ontology development of food and nutrition for ore-school that aims to assist pre-school in daily diet selections based on Thai foods menus and nutrition guidelines. This research reused existing ontologies and resources to present the ontology modeling and rules-based that focus on Thai pre-school. The methodology of this research can be summarized into four major states; data collection, ontology development, rules-based development, and evaluation. The eight main classes of this ontology are Body Mass Index (BMI) levels, Thai foods menus, Food energy levels, and knowledge base for providing the recommendation based on BMI level for Thai pre-school. In addition, the evaluation result from domain experts ensured that this ontology and rules-based can be used in Thai food menu recommendation system for Thai pre-school.Â Â Â